2019
DOI: 10.1096/fj.201802811r
|View full text |Cite
|
Sign up to set email alerts
|

TRPC6 regulates phenotypic switching of vascular smooth muscle cells through plasma membrane potential‐dependent coupling with PTEN

Abstract: Vascular smooth muscle cells (VSMCs) play critical roles in the stability and tonic regulation of vascular homeostasis. VSMCs can switch back and forth between highly proliferative synthetic and fully differentiated contractile phenotypes in response to changes in the vessel environment. Although abnormal phenotypic switching of VSMCs is a hallmark of vascular disorders such as atherosclerosis and restenosis after angioplasty, how control of VSMC phenotypic switching is dysregulated in pathologic conditions re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 41 publications
1
30
1
1
Order By: Relevance
“…24 Many vascular diseases, such as atherosclerosis and restenosis, are closely associated with phenotypic changes from the contractile to synthetic phenotype for VSMCs. 25,26 Furthermore, a-SMA, SM myosin heavy chain, vimentin, and collagen I have been found as phenotypic markers for VSMCs. 27e29 Also, corpus cavernosum is considered as a specific vascular tissue with phenotypic transformation.…”
Section: Discussionmentioning
confidence: 99%
“…24 Many vascular diseases, such as atherosclerosis and restenosis, are closely associated with phenotypic changes from the contractile to synthetic phenotype for VSMCs. 25,26 Furthermore, a-SMA, SM myosin heavy chain, vimentin, and collagen I have been found as phenotypic markers for VSMCs. 27e29 Also, corpus cavernosum is considered as a specific vascular tissue with phenotypic transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the TRPC6 expression level positively correlated with the increased coronary artery contractility [ 153 ]. However, an in vitro study demonstrated that TRPC6 activity promoted phenotypic switching in vascular smooth muscle cells from the contractile phenotype to the highly proliferative “synthetic” phenotype through plasma membrane potential-dependent coupling with PTEN [ 154 ]. Conversely, inhibition of TRPC6 facilitated contractile differentiation of vascular smooth muscle cells [ 154 ].…”
Section: Physiological and Pathological Functions Of Trpcs Revealementioning
confidence: 99%
“…However, an in vitro study demonstrated that TRPC6 activity promoted phenotypic switching in vascular smooth muscle cells from the contractile phenotype to the highly proliferative “synthetic” phenotype through plasma membrane potential-dependent coupling with PTEN [ 154 ]. Conversely, inhibition of TRPC6 facilitated contractile differentiation of vascular smooth muscle cells [ 154 ]. The TRPC3 channel, a member of the same TRPC3/6/7 subgroup, was also found to facilitate phenotypical switch and proliferation of human smooth muscle cells from the coronary artery and aorta in vitro, and TRPC3 inhibition with Pyr3 decreased smooth vascular muscle proliferation [ 155 ].…”
Section: Physiological and Pathological Functions Of Trpcs Revealementioning
confidence: 99%
“…The role of TRPC6 in the expression of contractile biomarkers may vary between the basal state and agonist-induced differentiation. A recent study by Numaga-Tomita et al 31 shows that transforming growth factor-b1-stimulated contractile differentiation and expression of SM22 is enhanced in aortic SMC harvested from TRPC6 −/− mice compared with WT mice. No difference is seen in the basal expression of SM22 between serum-starved WT and TRPC6 −/− aortic SMC, which contrasts with our findings with SMC grown in serum-supplemented medium.…”
Section: Discussionmentioning
confidence: 96%